2015
DOI: 10.1152/ajpendo.00601.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipopolysaccharides on adipogenic potential and premature senescence of adipocyte progenitors

Abstract: Zhao M, Chen X. Effect of lipopolysaccharides on adipogenic potential and premature senescence of adipocyte progenitors. Am J Physiol Endocrinol Metab 309: E334 -E344, 2015. First published June 23, 2015; doi:10.1152/ajpendo.00601.2014.-The elevation of circulating LPS has been associated with obesity and aging. However, whether and how LPS contributes to adipose tissue dysfunction is unclear. In this study, we investigated the effect of LPS on the adipogenic capacity and cellular senescence of adipocyte proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…LPS is an endotoxin, that may not necessarily increase lipid content in adipocytes but serves as a ligand for TLR4 induced inflammatory pathways [32] that may eventually inhibit adipocyte differentiation. It could be speculated that only adipocyte differentiation was affected directly by TLR4 activation or through lipid metabolism which may be in contrast to some other studies due to differences in LPS treatment periods [60]. However, the lack of cell count after the differentiation process might be a limitation in our study.…”
Section: Discussionmentioning
confidence: 75%
“…LPS is an endotoxin, that may not necessarily increase lipid content in adipocytes but serves as a ligand for TLR4 induced inflammatory pathways [32] that may eventually inhibit adipocyte differentiation. It could be speculated that only adipocyte differentiation was affected directly by TLR4 activation or through lipid metabolism which may be in contrast to some other studies due to differences in LPS treatment periods [60]. However, the lack of cell count after the differentiation process might be a limitation in our study.…”
Section: Discussionmentioning
confidence: 75%
“…“Replicative senescence” is associated with the cellular aging process affected by telomere shortening [ 35 , 41 ]. In contrast, “premature senescence” is induced by stressors such as oxidative stress and ROS without telomere-independent mechanisms [ 51 , 57 ]. Our previous study indicated that telomere length was not associated with adipocyte hypertrophy from three anatomical sites (subcutaneous, visceral and intramuscular) in obese cattle [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that senescent adipose-derived stromal/progenitor cells in response to an adipogenic hormone cocktail show reduced expression of key adipogenic regulators and impaired expression of adipogenic differentiation genes, including adiponectin (Mitterberger et al 2014 ). In another study, Zhao and Chen investigated whether elevated lipopolysaccharides (LPS) which has been associated with obesity, contribute to induction of cellular senescence and impaired adipogenic capacity (Zhao and Chen 2015 ). Stromal-vascular cells isolated from adipose tissue of mice subjected to LPS underwent induction of cellular senescence and a decrease in expression of adipocyte marker genes.…”
Section: Cellular Senescence As a Driver Of Metabolic Diseasesmentioning
confidence: 99%